Exploring College of Education Students' Aversion to Teaching. - Al-Busaidi, Saleh (Pertanika Journal of Social Sciences & Humanities, 2019)
This study sought to ascertain the intentions of College of Education students towards the teaching profession using a questionnaire. The sample consisted of 464 students drawn from nine education majors at the College of Education at Sultan Qaboos University, Sultanate of Oman. The study revealed that while many of the students intended to join the teaching workforce, a fairly large portion did not seem to share the same interest. There is a range of internal and external factors that contribute to the positive and negative views students develop about teaching. Students' views reflected their perceptions about the status of the teacher and teaching in general. The study concluded that despite being admitted to the College of Education, student teachers were vulnerable to internal and external factors that could affect their decision and destination and consequently impact employment plans to fill the many teaching vacancies in the country. This research has important implications for pre-service and in-service teachers, teacher educators, researchers and policy makers, all of whom play a crucial role in enhancing the quality of the teaching workforce. While this study was conducted in Oman, its implications are applicable globally as teacher shortages have become a wide-reaching concern.